RANCANG BANGUN SISTEM INFORMASI AKADEMIK SMP NEGERI 5 KOTA KUPANG BERBASIS WEB - Hizkia Marlon Daud (STIKOM Uyelindo Kupang, 2022)
The technology in the computer field is currently growing rapidly to increase the efficiency and effectiveness of any job. Computers not only process data and images, their use is becoming more and more widespread and has become a medium of communication, information and education. An EDP system can be used more easily if it is equipped with a more precise system with the main data to be used, including the use of a web-based science information system. A web-based science information system is a facility in a computerized system that is equipped with functions and designed to be suitable for the input of certain data for the purpose of speeding up and speeding up the data input has been used by the inexperienced user. Information systems have become the most important choice for providing and searching for information on specific data. Public junior school 5 Kupang City is one of the schools in need of a web-based academic information system. Schools as a state authority in the education sector do a lot of data management in data administration, both student, teacher and personal data. The writer is creating a web-based academic information system that will allow the grading system to be changed from a manual to a computerized system. The software developed in this study uses PHP and MySQL as database servers, which are then tested for their feasibility so that an effective and efficient academic information system can be used at the public junior 5 Kupang City. Keywords: academic, information system, web.